Trends and Challenges in Educational Equity Research under China's Double Reduction Policy: A Bibliometric Analysis - Qiuyan Zhang (Ilmu Inovasi Nusantara, 2025)
Educational equity (EE), including China, has become a critical issue in global education policies. Implementing the